Dissemination Strategies for Research Support Services at Vrije Universiteit and Experiences from Dutch University Libraries - Both, Joeri (REBIUN, 2026)
Vídeo del workshop: https://www.youtube.com/watch?v=9tji3qpc0So , minuto 00:18:00
Keywords: Servicios de apoyo a la investigación; Bibliotecas universitarias